2016
DOI: 10.1186/s40064-016-2351-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities of docetaxel: original drug versus generics—a comparative study about 81 cases

Abstract: IntroductionDocetaxel is a chemotherapy drug widely prescribed in oncology that recognizes a variety of manufactured generics whose toxicity is increasingly reported. The aim of this study was to compare the toxicities between the original and a generics docetaxel in a Moroccan center.MethodsIn a cross sectional study, we enrolled patients treated with docetaxel from the oncology department of the military hospital of Rabat over a period of 2 years (2013–2014). We compared the prevalence of hypersensitivity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The synergy of the PAD2 inhibitor and docetaxel was also confirmed in tumor growth in vivo. High-dose docetaxel therapy was found to be associated with safety issues among clinical trial patients and effective strategies to decrease the dosage are urgently needed [5, 10]. Therefore, our drug regimen may provide a better therapeutic strategy to reduce the dose of docetaxel used for those patients with tamoxifen-resistant breast cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergy of the PAD2 inhibitor and docetaxel was also confirmed in tumor growth in vivo. High-dose docetaxel therapy was found to be associated with safety issues among clinical trial patients and effective strategies to decrease the dosage are urgently needed [5, 10]. Therefore, our drug regimen may provide a better therapeutic strategy to reduce the dose of docetaxel used for those patients with tamoxifen-resistant breast cancer in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies also showed that combination of docetaxel with other cancer drugs yields good results [5]. However, cumulative systemic toxicity after prolonged and high-dose therapy was found to be associated with safety issues among clinical trial patients including hematological issues, asthenia, cutaneous reactions, and neurosensory reactions [5, 10]. Clearly, it is of high clinical significance to enhance the efficacy of docetaxel using lower doses in a less toxic manner and to reduce its side effects.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies used Tween 80 and ethanol as vehicles for docetaxel, which are from marketed docetaxel (18,19), while 0.1% dimethyl sulfoxide was used as a vehicle in this study. Although Tween 80 and ethanol are generally regarded to be biocompatible, the combination of Tween 80 and ethanol is well known for its nonspecific toxicity and may enhance the toxicity of docetaxel (20,21). Further study is needed regarding the hemolytic properties of docetaxel and Nanoxel.…”
Section: Discussionmentioning
confidence: 99%
“…There have been an increasing number of generic docetaxel toxicities in comparison to the original drug formulation. Impurities, excipients, and the amount of active agent itself can all have an impact on the efficacy of the drug and impact its narrow therapeutic index resulting in increased side effects [2].…”
Section: Discussionmentioning
confidence: 99%